2019
DOI: 10.1111/1442-1984.12236
|View full text |Cite
|
Sign up to set email alerts
|

Is phenotypic plasticity an explanation for the invasiveness of goldenrods (SolidagoandEuthamia) in Europe?

Abstract: High phenotypic plasticity contributes to invasiveness of alien species. Goldenrods of American origin (Solidago canadensis, S. gigantea and Euthamia graminifolia) have successfully invaded Europe, and this success can be related to their high phenotypic plasticity. The aim of our study was to test the hypothesis of higher phenotypic plasticity of invasive goldenrods by comparing them with native taxa: closely related Solidago virgaurea and similar ecologically, invasive in other regions Tanacetum vulgare. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 72 publications
2
8
0
Order By: Relevance
“…Wang, Li, Zhou, and Yan (2016) investigated 515 invasive plant species in China, and at least 196 (38.1%) were clonal plant species. The rank for species invasiveness significantly depended on the presence of rhizomes (Szymura, Szymura, Rajsz, & Świerszcz, 2019). This finding suggests that when the breeding system of alien plants is self‐incompatible, the combination with the presence of rhizomes should be given attention in risk assessment protocols for plant invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Wang, Li, Zhou, and Yan (2016) investigated 515 invasive plant species in China, and at least 196 (38.1%) were clonal plant species. The rank for species invasiveness significantly depended on the presence of rhizomes (Szymura, Szymura, Rajsz, & Świerszcz, 2019). This finding suggests that when the breeding system of alien plants is self‐incompatible, the combination with the presence of rhizomes should be given attention in risk assessment protocols for plant invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Both studies showed that high phenotypic plasticity is an important trait contributing to the invasiveness of S. canadensis . However, Szymura et al (2019) found that the invasion success of non‐native goldenrods is not caused by their having higher phenotypic plasticity than native species in response to different substrates with different fertilizers. There are several possible explanations for the difference in phenotypic plasticity between China and Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, although there is no direct evidence, the distance between the invaded site and origin sites may also have some impacts on the phenotypic plasticity. Third, for environmental stress, three different types of substrates were selected in Szymura et al (2019), whereas the extrinsic factor (i.e., temperature and N) was selected in our study. Obviously, we cannot rule out other possibilities, such as experimental manipulation, species quantity, calculation method, and local habitat, for this difference.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations